PENGARUH PENYULUHAN GIZI TENTANG PENCEGAHAN OBESITAS DENGAN MEDIA FILM ANIMASI TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP ANAK SEKOLAH SD MUHAMMADIYAH 01 PEMATANGSIANTAR - Ratih Oktri Nanda; Ernawati Nasution; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The rapid development caused shifting in the lifestyle and diet of primary school students. Their physical activity is decreasing due to the use of technology and they tend to eat high in fat and carbohydrates meals that can lead to obesity. Based on those problem, nutrition counseling is made using an interesting media to deliver nutrition information easily, particularly in obesity prevention. This study aims to determine the effect of nutrition counseling on obesity prevention using animated movie media to increase the knowledge and attitude of SD Muhammadiyah 01 Pematangsiantar students. This research is a quasi-experimental design with pre- and post- test group design. Sampling was carried out with a purposive sampling method with a sample of 85 children with one treatment group. Data was collected by using questionnaires. Data analysis using the Wilcoxon test at 95% significance level.The results showed knowledge of students in pre-test scores on the category of less is 7,1% and 0,00% in post-test scores. The results also showed the attitude of students in pre-test score on the category of less is 15,3% and 0,00% in post-test scores. The result of statistical test showed an improvement in score of knowledge and attitude after watching the animated movie. The results of the analysis of differences in knowledge and attitude before and after the animated movie screening showed a significant difference (p.=0,000). The conclusion of this study is health counseling using animated movie increase the knowge and attitude of primary school on obesity prevention. The suggestion of this research is that the animated movie could be used by health workers to deliver information about obesity prevention to students and the school can used this animated movie to as a media to deliver nutrition information about obesity in the learning process. Keywords: animated movie, obesity prevention, knowledge, attitude, primary school children